Sub-cycle metallization of SiO2 nanoparticles probed via carrier-envelope phase dependent electron acceleration - Liu, Q.; Zherebtsov, S.; Süßmann, F.; Passig, J.; Seiffert, L.; Mondes, V.; Kessel, A.; Trushin, S.; Graf, C.; Rühl, E.; Tiggesbäumker, J.; Meiwes-Broer, K. H.; et al. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
We employ few-cycle pulses (4.5 fs duration centered at 720 nm) with controlled carrier-envelope phase (CEP) to probe the metallization of 95 nm diameter SiO2 nanoparticles. The momenta of photoemitted electrons from nanoparticles are recorded via high-energy Stereo Time-Of-Flight (Stereo-TOF) spectroscopy for each laser shot.
CRIS-Team Scopus Importer:2023-04-20